Key Factors Affecting Valuation Accuracy for Petrol Filling Stations - Mohd Khairulanis, Muhamad Khairul Amin; Kasim, Rozilah (Research in Management of Technology and Business, 2025)
Valuation of petrol filling stations is critical for making iformed investment decisions ad accurate financial reporting. Petrol filling stations provide essential services to consumers, including the sale of fuel, convenience store items, car washes and vehicle maintenence. However, there are significant valuation errors, biases ad variatios stemming from differig methodologies ad market expectations. To enhance the valuation accuracy of petrol stations, it is essential to identify and address these infuencing factors systematically. This researcch aims toidentify factors ad evauate the most sigificat factors affecting the accuracy of valuing petrol filling stations. This reserch adopted the quantitative method, which involves distributing questionnaires to the 100 respodents consisting of valuer and assistant valuer officers of the Department of Valuation and Property Services (JPPH) in Selangor. The data obtained was cimputed using SPSS sofware as descriptive analysis. This reseach findings reveal four factors affecting the valuation accuracy for petrol filling stations, with the ’Valuation Method’ factor being the most crucial in achieving more accurate in valuing these type of properties. The findings serve as a guide and reference for the JPPH to compute and value petrol silling stations accurately.